Association between the Quality and Diversity of Diet and the Risk of Colorectal Cancer - Saeed Karimdavijani; Afsaneh Ahmadi; Moein Askarpour; Bahram Rashidkhani (International Journal of Nutrition Sciences, 2025)
Background: Colorectal cancer is the third-most common cancer in the world. Diet is one of the most important factors in colorectal cancer prevention. This study examined the association between the diet quality and diversity and the risk of colorectal cancer.Methods: In a case-control study, 213 participants comprising 71 cases and 142 controls were enrolled. A semi-quantitative, 125-item frequency questionnaire was used to collect dietary information. The Food Quality Score (FQS) and Dietary Diversity Score (DDS) were employed to check the diet quality and variety. Logistic regression determined the relationship between the quality and diversity of diet and the risk of colorectal cancer.Results: Between the highest and lowest tertiles of the FQS, the risk of colorectal cancer dropped significantly (OR=0.28, 95% confidence interval (95%CI): 0.13-0.61, p=0.001). This trend continued when all confounders were considered in the adjusted model (OR=0.07, 95%CI: 0.02–0.22, p<0.001). For the DDS in the crude model, the last tertile when compared to the first tertile, a decreasing trend was observed for the risk of colorectal cancer (OR=0.37, 95%CI: 0.18–0.79, p=0.001). After adjusting for confounding factors in the adjusted model, the odds of colorectal cancer decreased with a more diversified diet (OR=0.30, 95%CI: 0.11-0.82, p=0.019).Conclusion: The results revealed that a diet with high quality and diversity had a preventive role in reducing the risk of colorectal cancer.